Results of the study of pH and organic matter in the surface soil of Ulaanbaatar - Tsagaan, Byambasuren; Ganbaatar, Ochirbat; Otgonbayar, Azzayaa (Proceedings of the Mongolian Academy of Sciences, 2021)
This work summarizes the results of a study into such important urban soil parameters as soil actual (pH) and potential acidity (pH) and soil organic matter content (SOM) in the surface soil of Ulaanbaatar. The soil pH in Ulaanbaatar is slightly alkaline, with a median pH value of 7.36 (actual acidity) and 6.93 (potential acidity), and they were found to be the highest in the industrial zone as compared to other zones in the city. The median value of organic matter content in Ulaanbaatar surface soil was 5.61%, with a high variability in the industrial (C.V.-119%) and transport (C.V.-55.34%) zones. The SOM mean value in urban soil is less than the background value in surface soil from natural area, indicating to increasing compaction and reduction of porosity of soil in urban areas. Also, organic matter content have decreased relatively to previous data, reflecting the urbanization process and such long-term processes as aerial urban fallout.